2022
DOI: 10.3390/nano12050830
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis of Silver Nanoparticles Using Phagnalon niveum and Its In Vivo Anti-Diabetic Effect against Alloxan-Induced Diabetic Wistar Rats

Abstract: Background: Type-2 diabetes mellitus (T2DM) is a non-communicable, life-threatening syndrome that is present all over the world. The use of eco-friendly, cost-effective and green synthesised nanoparticles (NPs) as a medicinal therapy in the treatment of T2DM is an attractive option. Aim: The present study aimed to evaluate the anti-diabetic potential of the phyto-synthesised silver nanoparticles (AgNPs) obtained from Phagnalon niveum plant methanolic extract. Methods: The green synthesised AgNPs made from Phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Currently available treatment options for diabetes mellitus are achieved through oral hypoglycemic agents (metformin, sulfonylureas, and thiazolidinediones), insulin therapy, dietary guidance, and regular physical activity [7,8]. Unfortunately, their use is limited by adverse effects including gastrointestinal disorders, hypoglycemia, pancreatic degeneration, liver damage in the body [9], failure to achieve glycemic control, a different drug response among individuals [8,10] and cardiovascular disorders [9]. Moreover, antidiabetic drugs have become very expensive due to the high cost of treatment and these constraints lead people in developing countries to turn to traditional medicine for their primary health care keeping.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available treatment options for diabetes mellitus are achieved through oral hypoglycemic agents (metformin, sulfonylureas, and thiazolidinediones), insulin therapy, dietary guidance, and regular physical activity [7,8]. Unfortunately, their use is limited by adverse effects including gastrointestinal disorders, hypoglycemia, pancreatic degeneration, liver damage in the body [9], failure to achieve glycemic control, a different drug response among individuals [8,10] and cardiovascular disorders [9]. Moreover, antidiabetic drugs have become very expensive due to the high cost of treatment and these constraints lead people in developing countries to turn to traditional medicine for their primary health care keeping.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD graph was plotted by intensity vs. 2θ. In the spectrum, the sharp peaks show crystalline [ 13 , 14 ] in which atoms were arranged in a periodic pattern of three dimensions (3D). The variation of peaks in XRD spectrum was due to doping or foreign atoms capping, so it confirmed the synthesis of the composite [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plant entities used as in production and assembly of AgNPs have gained attention due to their quick, non-hazardous, eco-friendly, and economical protocol, as they provide a simple, single-step technique for the biosynthesis of nanoparticles [ 12 ]. Finding novel hypoglycemic medications with fewer side effects along with better effectiveness is a worthwhile endeavor, and this has been the focus of previous study [ 13 ]. Biologically inspired green synthesis of nanoparticles has become a promising alternative against the chemically fabricated process considering reduced toxicity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also caused due to changes in food and lifestyle. A recent investigation reported that silver NPs synthesized from Phagnalon niveum methanol extract demonstrated antidiabetic activity by reducing the blood glucose level and also reduced the body weight of rats in 1 to 21 days [ 178 ]. Spherical shaped-CuO NPs synthesized from Silybum marianum seed extract displayed great enzymatic inhibitory activity against ureases, alpha-amylase, and lipases so it was concluded that they can act as antidiabetic agents [ 179 ].…”
Section: Application Of Asteraceae -Based Nanopart...mentioning
confidence: 99%